The role of extra-curricular sports activities on mental health For secondary school pupils in Laghouat"A field study " - medjadi, Mustafa; Abedelkarim , meliani; dehina, Mohamed radhouane (sports creativity, 2025)
The aim of this study was to highlight the role of practicing non-classroom sports activities in the psychological health of pupils in the secondary school stage in Laghouat city, where the analytical descriptive approach was used, a sample of 260 pupils from the pupils of the school school school's high school grades 2018/2019 was randomly selected and the data was gathered with a tool of resolution. Among the most important results are: There is a link between a practice. Classroom sports and psychological health activities of practicing students. There are statistically significant differences between practitioners of non-mental health sports activities in students. It was in the interests of practitioners